Digital Segusio: from models generation to urban reconstruction - Antonia Spanò; Filiberto Chiabrando; Livio Dezzani; Antonio Prencipe (Virtual Archaeology Review)
The reconstructive study of the urban arrangement of Susa in the 4th century arose from the intention to exploit some resources derived from local studies, and survey activities, fulfilled by innovative methods from which the modelling of architectural heritage (AH) and virtual reconstructions are derived.  The digital Segusio presented in this paper is the result of intensive discussion and exchange of data and information during the urban landscape documentation activities, and due to the technology of virtual model generation, making it possible to recreate the charm of an ancient landscape. The land survey has been accomplished using aerial and terrestrial acquisition systems, mainly through digital photogrammetry from UAV (Unmanned Aerial Vehicle) and terrestrial laser scanning.  Results obtained from both the methods have been integrated into the medium scale geographical data from the regional map repository, and some processing and visualization supported by GIS (Geographical Information System) has been achieved. Subsequently, with the help of accurate and detailed DEM (Digital Elevation Model) and other architectural scale models related to the ancient heritage, this ancient landscape was modelled. The integration of the history of this city with digital and multimedia resources will be offered to the public in the city museum housed in the restored castle of Maria Adelaide (Savoy dynasty, 11th century), which stands in the place where the acropolis of the city of Susa lay in ancient times.